Strain‐Induced Interlayer Parallel‐to‐Antiparallel Magnetic Transitions of Twisted Bilayers. Issue 3 (12th January 2021) - Wang, Jian‐Jun; Yang, Tian‐Nan; Wang, Bo; Rzchowski, Mark S.; Eom, Chang‐Beom; Chen, Long‐Qing
Abstract: The discovery of superconductivity in twisted graphene bilayers with a magic twisting angle ≈1.1° has opened up a wide range of potential twistronic device possibilities. In this work, the twisting effects in spintronic devices are explored. In particular, a material prototype integrating spintronics, straintronics, and twistronics is developed by stacking a twisted CoFe2 O4 (CFO) bilayer membrane on a Pb(Mg1/3 Nb2/3 )O3 ‐PbTiO3 (PMN‐PT) membrane. Phase‐field simulations are performed to study the magnetic domain configurations and switching in CFO bilayers under piezostrains. An emerging interlayer parallel‐to‐antiparallel magnetic transition of the twisted CFO bilayer induced by appropriate piezostrain pulses generated from the PMN‐PT membrane is discovered. Such a strain‐induced parallel‐to‐antiparallel magnetic transition is non‐volatile and reversible, arising from the synergistic interaction among spin, strain, and twisting order parameters. The present work provides a paradigm for designing novel spinotropic devices by taking advantage of the emerging phenomena generated by twisting. Abstract : A material prototype integrating spintronics, straintronics, and twistronics is developed by stacking a twisted CoFe2 O4 (CFO) bilayer membrane on a Pb(Mg1/3 Nb2/3 )O3 ‐PbTiO3 (PMN‐PT) membrane. Phase‐field simulations reveal an emerging non‐volatile and reversible interlayer ferro‐to‐antiferro magnetic transition of the twisted CFO bilayer induced by appropriate piezostrain pulses generated from the PMN‐PT membrane. This work provides a paradigm of designing novel spinotropic devices.